Effectiveness of Web-Based Problem-Based School Administrator Training Program and its Effect on Participants' Attitudes towards Web-Based Learning - Karabatak, Songul; Turhan, Muhammed (Pegem Akad Yayincilik Egitim Danismanlik Hizmetleri Tic Ltd Sti, 2017)
The aim of this study is to determine the effectiveness of a web-based problem-based school administrator training program (WB-PBSAT) in practice and the effect of training on participants' attitudes towards web based learning. Mixed method approach was used in this study. While the quantitative dimension of the study was conducted within the framework of one group pre-test post-test experimental design, focus group interviews was performed in the qualitative dimension. Participants of the experimental and the control groups were determined by purposive sampling. Attitudes Toward Web-Based Learning (ATWBL) Scale was used to determine the participants' attitudes towards web-based learning, and the Program Assessment Scale was used to evaluate the training process. According to the findings it was concluded that the training process positively affected the attitudes of the participants towards web-based learning and training process has also provided significant contributions to participants' establishing the link between theory and practice and self-directed learning. Based on these results, some suggestions for educational policy makers and practitioners were developed for the use of a web-based problem-based learning in school administrators' pre-service and in-service training programs.
Web tabanli problem temelli okul yöneticisi egitim programinin uygulamadaki etkililigi ve katilimcilarin Web Tabanli ögrenmeye Yönelik tutumlarina etkisi
Keywords: School administrator; School administrator development; School administration training; Web based learning; Problem based learning